Perfil emocional de cafés (Coffea arabica L.) produzidos no maciço de Baturité – CE e desenvolvimento da roda de emoções do provador de café - Souza, Clarisse Machado de (2019)
Coffee production from Maciço de Baturité-CE has specific flavor characteristics provided by the terroir, and its organic, agroforest and shade conditions with the whole production chain are locally detained, being relevant to understand how they are perceived by consumers. Sensorial quality is the most relevant factor in consumer choice and purchase determination, but traditional analyses focused on acceptance have proven unable to predict choice and purchase intention. Therefore, studies have been exploring more unconscious responses preceding the cognitive process for evaluation, such as emotional responses. This study analyzed the physical-chemical characteristics and the emotional profile of four coffee samples produced in Maciço de Baturité-CE by conducting two focus groups and applying the RATA technique. The samples presented moisture content at recommended levels, except for sample 4, which was over the recommendation. This sample was the only one to present thinner granulometry than the other samples, as well as lower grades on the acceptance evaluation. The pH values were slightly above the pattern described as ideal, while the roasting degree, compared by L* with other studies, showed to be medium in all the samples. The samples did not vary regarding acceptance (slightly liked), except for sample 4 which was evaluated as indifferent. Related to this aspect, consumers were clustered by ACH and presented different emotional patterns and variations regarding what influences acceptance/rejection of the samples. Terms in the PCA tended to present specific cartesian organization, corresponding to the affect variation of both valence and arousal. The Coffee Taster Emotion Wheel was developed according to the correlation among the emotional terms and systematically organized according to basic emoticon categories, guided by the affect variation in both dimensions.